2023
DOI: 10.1021/acs.est.3c01986
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anaerobic Wastewater Treatment by a Binary Electroactive Material: Pseudocapacitance/Conductance-Mediated Microbial Interspecies Electron Transfer

Abstract: Anaerobic digestion (AD) is a promising method to treat organic matter. However, AD performance was limited by the inefficient electron transfer and metabolism imbalance between acid-producing bacteria and methanogens. In this study, a novel binary electroactive material (Fe 3 O 4 @biochar) with pseudocapacitance (1.4 F/g) and conductance (10.2 μS/cm) was exploited to store-release electrons as well as enhance the direct electron transfer between acid-producing bacteria and methanogens during the AD process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 47 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…This stimulatory effect may be ascribed to the establishment of DIET between G. grbiciae and M. barkeri 800 with conductive particle materials acting as electron conduits. Previous studies on DIET have indicated that some (semi) conductive materials (including magnetite, carbon cloth, GAC, and biochar) can accelerate the direct electron transfer between microbes [7,10,13,[18][19][20][21][22][23][24][25][26][27]34,35]. Methane was generated at a faster rate and higher levels in co-cultures supplemented with GAC than in co-cultures supplemented with magnetite during the early growth phase.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This stimulatory effect may be ascribed to the establishment of DIET between G. grbiciae and M. barkeri 800 with conductive particle materials acting as electron conduits. Previous studies on DIET have indicated that some (semi) conductive materials (including magnetite, carbon cloth, GAC, and biochar) can accelerate the direct electron transfer between microbes [7,10,13,[18][19][20][21][22][23][24][25][26][27]34,35]. Methane was generated at a faster rate and higher levels in co-cultures supplemented with GAC than in co-cultures supplemented with magnetite during the early growth phase.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequently, various co-cultures that exchange electrons through DIET have been reported [5,[12][13][14][15][16][17][18] and primarily involve Geobacter species and methanogens. Moreover, the effects of various conductive materials on DIET have also been reported [7,10,[18][19][20][21][22][23][24][25][26][27]. The continuing increase in the number of microbes identified to carry out electron exchange through DIET indicates that DIET is a syntrophic metabolism that is more prevalent in nature than previously thought.…”
Section: Introductionmentioning
confidence: 91%
“…It was reported that biopseudocapacitance exhibited by EBs enables rapid biofilm enrichment and facilitates efficient nitrate reduction in a bioelectrochemical denitrification system . It was also demonstrated that the pseudocapacitive and conductive mediators regulated the interspecies electron transfer rates (acid-producing bacteria and methanogens) and highly improved methane production in anaerobic digestion systems . These findings provide a new understanding of the regulation of biological metabolism processes involving electroactive biofilms centered on exoelectrogens.…”
Section: Environmental Implications and Future Perspectivesmentioning
confidence: 87%
“…Due to the poor capacity of methanogens to degrade organic macromolecules and bacteria (anaerobic microorganisms and acidogenic bacteria) can hardly generate methane, an efficient AD process requires balanced syntrophic metabolism between various microorganisms with fast electron exchange. A higher electron transfer rate during AD can lead to a faster mutualistic metabolism process between various functional bacterial species, improving the VFAs and H 2 production rate during the acidification process and the VFAs consumption rate to produce CH 4 during the methanogenesis process. , In another word, the electron transfer rate during the AD process is a principal factor that influence the functional bacteria activity as well as the VFAs generation and consumption rate, thus determining the final biohythane production rate …”
Section: Introductionmentioning
confidence: 99%